Breakdown Characteristic For Various Type Of Rubber - Sahbudin, Mohammad Faizul (UTeM, 2009)
Rubber as solid insulating materials is used in many electrical applications. In all such applications, the electrical insulation ability of the rubber is of primary importance. Hence, the purpose of this project is to study the breakdown characteristic for various types of rubber. The types of rubber that had been selected for this project are natural rubber (NR), styrene butadiene rubber (SBR) and butyl rubber (IIR). In this project, the high voltage testing was conducted based on IEEE standard. By using Hafely construction KIT, AC and DC voltage breakdown tests and AC, DC and Impulse withstand voltage tests were conducted. The testing procedure focuses on 1 stage of high voltage configuration which the voltage can be generated up to 100kV. The experimental result will be analyzed to calculate the dielectric strength of the selected rubber in order to know the performance of the rubber as an insulating material. From the experimental results, it has indicated that NR has lower breakdown voltage strength compared to SBR and IIR. It also discovered that treeing phenomenon occurred on SBR and IIR under DC voltage breakdown tests.